2015
DOI: 10.1007/s00253-015-6670-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of paraffin oil on the interaction between denitrifying anaerobic methane oxidation and Anammox processes

Abstract: Methane is sparingly soluble in water, resulting in a slow reaction rate in the denitrifying anaerobic methane oxidation (DAMO) process. The slow rate limits the feasibility of research to examine the interaction between the DAMO and the anaerobic ammonium oxidation (Anammox) process. In this study, optimized 5 % (v/v) paraffin oil was added as a second liquid phase to improve methane solubility in a reactor containing DAMO and Anammox microbes. After just addition, methane solubility was found to increase by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…1). A similar growth pattern has been reported in previous studies for different NAPs, where bacteria were able to accumulate in the aqueous-NAP interphase and grow inside NAPs forming aggregates (Fu et al, 2015;Han et al, 2009b;Yamashita et al, 2007). Moreover, MacLeod and Daugulis (2005) observed that certain hydrophobic bacteria formed aggregates in the aqueous phase instead of inside the NAP.…”
Section: Resultssupporting
confidence: 87%
“…1). A similar growth pattern has been reported in previous studies for different NAPs, where bacteria were able to accumulate in the aqueous-NAP interphase and grow inside NAPs forming aggregates (Fu et al, 2015;Han et al, 2009b;Yamashita et al, 2007). Moreover, MacLeod and Daugulis (2005) observed that certain hydrophobic bacteria formed aggregates in the aqueous phase instead of inside the NAP.…”
Section: Resultssupporting
confidence: 87%
“…Prior to microscopy, the microorganisms immobilized in gels were fixed with 4% (w/v) paraformaldehyde at 4 °C for 2 h and then washed with 1× phosphate-buffered saline (PBS). The microorganism immobilization system was stained with 4′,6-diamidino-2-phenylindole (DAPI) and cut into slices with a microtome (Leica CM1950, Wetzlar, Germany) . The slice was then transferred onto the well of a microscope slide just before observation.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The microorganism immobilization system was stained with 4′,6-diamidino-2-phenylindole (DAPI) and cut into slices with a microtome (Leica CM1950, Wetzlar, Germany). 31 The slice was then transferred onto the well of a microscope slide just before observation. A phase contrast microscope (Olympus IX81) was used to analyze the gel structures in the slices.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Ammonium was analyzed using a water quality autoanalyzer (ThermoFisher, Aquakem 200, Finland) based on the hydrazine reduction method, which was described in Fu's study. 23 The produced biogas was recorded daily by a gas meter. 24 The content of hydrogen in the headspace was determined with a Gas Chromatograph (Lunan model SP7890, China) equipped with a thermal conductivity detector and a 1.5 m stainless steel column packed with 5Å molecular sieve.…”
Section: Chemical Analysismentioning
confidence: 99%